Graphene and electric transport properties in graphene-superconductor interfaces (2011)
Graphene is a two dimensional carbon structure, which possesses unusual electronic properties, whose electrons are described by the Dirac equation. This material allows to establish an analogy between condensed matter and particle physics. The graphene production a few years ago has encouraged a great theoretical and experimental work in order to understand and manipulate its properties. Actually different junctions consisting of graphene-superconductor interfaces have been investigated, namely GS, GIS, SGS, IGS (I:insulator, G:graphene, S: superconductor), in which the existence of normal and specular Andreev reflections have raised great interest. In this paper we introduce the basic properties of graphene and we do a brief review of papers about graphene - superconductor interfaces.